Peran Strategis Bank Syariah dalam Mengupayakan Solusi bersama Permasalahan Akuntansi pada Usaha Mikro, Kecil, dan Menengah (UMKM) - Pujo Hariyanto (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2017)
Islam as a system of life for all mankind emphasizes the importance of justice in all aspects of life. Including in the economic aspect, Islam emphasizes the importance of upholding justice and eliminating injustice in every economic transaction. Therefore, Islam provides guidance on various provisions that need to be avoided so that economic transactions do not fall into injustice, including usury, maysir, gharar and unjust transactions. Instead, Islam replaces them with various forms of contracts that embody justice and brotherhood. In the context of the modern economy, economic institutions operating in Muslim societies should also always strive to realize these sharia-compliant contracts.